The conservation implications of mixed-species flocking in terrestrial birds, a globally-distributed species interaction network. (August 2018) - Zou, Fasheng; Jones, Harrison; Colorado Z., Gabriel J.; Jiang, Demeng; Lee, Tien-Ming; Martínez, Ari; Sieving, Kathryn; Zhang, Min; Zhang, Qiang; Goodale, Eben
Abstract: Conservation biologists now view species interaction networks as systems that should be targets of conservation, but there are few actual cases in which networks have formed the basis for management strategies. Terrestrial mixed-species bird flocks (hereafter, TMSF) represent one such potential system: they form throughout the world, and in most cases have an asymmetric organization in which one or a few species play 'nuclear' roles, being particularly important for flock formation or maintenance. A quantitative study on the distribution of TMSF and how they respond to anthropogenic disturbance (AD) is still, however, needed. We surveyed 201 publications on terrestrial TMSF worldwide, finding that 19% of the world's bird species participate in them, including 158 threatened species, with tropical species dominating these lists. Of 31 TMSF studies that investigated AD, 22 showed significant declines in some metric, with TMSF in more impacted areas including 1/4 fewer species, and 1/3 fewer individuals. In 13/15 studies, TMSF were more sensitive to AD than the overall bird community. We conceptualize the reasons behind this response: first, AD directly influences drivers of flocking (predation, foraging), and second, AD produces changes in community composition that affect TMSF, such as when the extirpation or reduction of nuclear species affects other species' participation. We rank nuclear species globally by their consistency of leadership and number of followers, suggesting that these species' interactive roles be considered as part of their conservation value, and further that conserving TMSF provides an efficient mechanism to ensure the protection of many species simultaneously. Highlights: Of global bird species, 19% have been recorded in terrestrial mixed-species bird flocks (TMSF). TMSF in more human-disturbed areas have 1/4 fewer species, 1/3 fewer individuals. Disturbance changes predation/foraging drivers, and pool of species that can join. 'Nuclear' species in TMSF may influence other species' fitness. We rank nuclear species by their consistency to lead and number of followers.